2006
DOI: 10.1111/j.1365-2109.2006.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of food selection and growth performance of koi carp, Cyprinus carpio L., and goldfish, Carassius auratus (L.) in mono- and polyculture rearing in tropical ponds

Abstract: further documentations relating to optimum stocking density and management of polyculture of ornamental carps are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
5
1
1
Order By: Relevance
“…Thus, goldfish had access to zooplankton as an additional food source, although the level was approximately one-third the amount found in the water of the supply pond (583 organisms/ L); this difference was possibly due to destruction of organisms in the water pump. The level of zooplankton available to goldfish in the present study was considerably lower than that reported for fertilized ponds used for aquaculture production of koi (domesticated common carp Cyprinus carpio) and goldfish (Jha et al 2006a(Jha et al , 2006b.…”
Section: Discussioncontrasting
confidence: 72%
“…Thus, goldfish had access to zooplankton as an additional food source, although the level was approximately one-third the amount found in the water of the supply pond (583 organisms/ L); this difference was possibly due to destruction of organisms in the water pump. The level of zooplankton available to goldfish in the present study was considerably lower than that reported for fertilized ponds used for aquaculture production of koi (domesticated common carp Cyprinus carpio) and goldfish (Jha et al 2006a(Jha et al , 2006b.…”
Section: Discussioncontrasting
confidence: 72%
“…Not surprisingly, the effectiveness of duoculture is dependent on the species concerned. For example, Atlantic salmon feed less, grow less well and have more fin damage when reared in duoculture with brown trout than when reared in monoculture , as do goldfish (Carassius auratus) reared in duoculture with koi carp (Cyprinus carpio; Jha et al 2006), because they are attacked by the trout and koi respectively.…”
Section: Manipulating Stimuli Experienced By Cultured Fishmentioning
confidence: 99%
“…Cyprinid larvae are known to prefer natural food items such as free-living protozoa and rotifers, and larger planktonic organisms like cladocerans and copepods at fry and fingerling stage (Jhingran and Pullin, 1985). Studies on feeding behaviour and food selection of koi carp and goldfish indicated a strong preference for cladocerans and negative selection of copepods and phytoplankton (Jha and Barat, 2005b;Jha et al, 2006b). Significantly higher growth and survival rates were observed in koi carp fry fed with exogenous plankton, compared with pelleted diet (Jha and Barat, 2005b;Jha et al, 2006a;Jha et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The koi carp, Cyprinus carpio are cultured at a density of 0.25 fish/l in Hawaii (reported in Asano et al, 2003) and 0.3 fish/l in India in outdoor tanks and ponds fed with either pelleted diet or live plankton (Jha and Barat, 2005a;Jha and Barat, 2005b;Jha et al, 2006a;Jha et al, 2007). The goldfish, Carassius auratus has also been cultured at a density of 0.3 fish/l in outdoor ponds and fed with live plankton (Jha et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%